The effect of unemployment on social participation of spouses - Evidence from plant closures in Germany - Lars Kunze; Nicolai Suppa (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
This paper estimates the effect of an individual's unemployment on the level of social participation of their spouse. Using German panel data, it is shown that unemployment has a strong negative effect on public social activities of both directly and indirectly affected spouses. Private social activities of either spouse, however, are only found to increase, if the indirectly affected spouse is not working. Conflict prevention strategies or habituation may help to rationalise this finding. Our results imply that active labour market policies should account for spillovers effects within couples and adopt a family perspective.
Keywords: J64; I31; 330; unemployment; social participation; plant closure; entropy balancing; SOEP